Recombinant SpTransformer proteins bind to specific sites on sea urchin phagocytes and modulate SpTransformer gene expression and immune responsiveness - Crow, Ryley S.; Grayfer, Leon; Smith, L. Courtney (Frontiers in Immunology, 2025)
IntroductionThe California purple sea urchin, Strongylocentrotus purpuratus, relies exclusively on an innate immune system to survive in its pathogen rich marine environment. Central to this defense is the SpTransformer (SpTrf) gene family that is unique to the euechinoid group of echinoderms. These genes were initially identified based on their striking upregulation in response to immune challenge. The SpTrf gene family encodes structurally similar proteins with a wide range of sequence diversity within and among individual sea urchins. A recombinant (r)SpTrf protein interacts specifically with a variety of non-self targets. Other rSpTrf proteins cross-linked to inert beads show distinct functions for cell binding and augmenting phagocytosis . However, whether the rSpTrf proteins bind to sea urchin phagocytes, and the cellular consequences of binding are largely unexplored. MethodsrSpTrf protein binding to, and responses by phagocytes was investigated by cytology, flow cytometry, binding competitions using In-cell ELISA, and gene expression analyses. ResultsSoluble rSpTrf proteins bind specifically and exclusively to both live and fixed polygonal and small phagocytes. The different rSpTrf proteins appear to bind shared receptor(s) or other form of cell surface binding site. The phagocyte response to bound rSpTrf proteins culminates in modulated expression of the SpTrf gene family as well as other immune-related genes. ConclusionsThese findings underscore the multifaceted and dynamic functions of SpTrf proteins within the innate immune system of the purple sea urchin. Their varied functions enable a robust immune response while also providing a unique modulatory mechanism by which response levels are controlled and adjusted to the level of the foreign threat.